2017
DOI: 10.1021/acs.est.6b05855
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Community Metagenomics in Two Different Anammox Configurations: Process Performance and Community Structure

Abstract: Anaerobic ammonia oxidation (anammox) combined with partial nitritation (PN) is an innovative treatment process for energy-efficient nitrogen removal from wastewater. In this study, we used genome-based metagenomics to investigate the overall community structure and anammox species enriched in suspended growth (SGR) and attached growth packed-bed (AGR) anammox reactors after 220 days of operation. Both reactors removed more than 85% of the total inorganic nitrogen. Metagenomic binning and phylogenetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 76 publications
6
45
0
1
Order By: Relevance
“…Anammox is catalysed by the sequential activity of the enzymes NIR, hydrazine synthase (HZS) and hydrazine dehydrogenase (HDH) (Kartal et al, 2013). All three enzymes are located in the anammoxosome, an intra-riboplasmic compartment (Niftrik et al, 2004;Kartal et al, 2011;Bagchi et al, 2016;Bhattacharjee et al, 2017). The lumen of the anammoxosome is separated by three single bilayer membranes from the environment (van Niftrik et al, 2008).…”
Section: Anaerobic Ammonia Oxidizing Bacteriamentioning
confidence: 99%
“…Anammox is catalysed by the sequential activity of the enzymes NIR, hydrazine synthase (HZS) and hydrazine dehydrogenase (HDH) (Kartal et al, 2013). All three enzymes are located in the anammoxosome, an intra-riboplasmic compartment (Niftrik et al, 2004;Kartal et al, 2011;Bagchi et al, 2016;Bhattacharjee et al, 2017). The lumen of the anammoxosome is separated by three single bilayer membranes from the environment (van Niftrik et al, 2008).…”
Section: Anaerobic Ammonia Oxidizing Bacteriamentioning
confidence: 99%
“…The microbial community in the biofilm carriers consisted of a diverse assemblage of taxa, many of which are typical for mainstream anammox WWTP 17, 18, 30 . Members of Proteobacteria, Chloroflexi, Planctomycetes and Actinobacteria dominated the biofilms, accounting for approximately 70% of the total community composition, However, Proteobacteria represented the largest Phylum of the community accounting for ∼40% of the total abundance (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…So far, the majority of these studies were focusing on how disturbances affect the autotrophic N removal efficiency on the process level but did not investigate effects on microbial guild dynamics and their respective stress response, which might have led to the observed performance failures and/or recovery processes. Metagenomic shotgun sequencing allows to gain a comprehensive insight in the functional potential of communities involved in the anammox process 17, 18, 30, 31 but is unlikely to yield useful information on short-term disturbance effects, which, in most of the cases, are not leading to shifts in the microbial community composition. Therefore we focus on biochemical measurements in combination with metatranscriptomics, which can provide important information on the response of microbes in a variable environment 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The larger fraction of HDB in the mainstream suggests more extensive 279 competition for NO2between AMX and HDB; in addition, potential nitrogen loops of nitrification, 280 anammox, denitrification and DNRA may occur (Speth, et al 2016). populations has also been reported in PNA systems (Bhattacharjee, et al 2017, Laureni, et al 2019, 318 Persson, et al 2014. Nitrospira is a heterogeneous group, which not only represents a nitrite 319 oxidising potential, but also contains populations capable of using a myriad of electron donors and -320 acceptors (Daims, et al 2015, Koch, et al 2015, van Kessel, et al 2015 and the same has also been 321 shown for AMX (Hu, et al 2019, Kartal, et al 2007, Strous, et al 2006 2008) and AOB (Bock, et al 1995).…”
Section: Sidestream and Mainstream Communities 270mentioning
confidence: 95%